FUNCTIONAL-SEMANTIC PROPERTIES OF GRADATION - M.M.Mirzakarimova; R.K.Adkhamova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The cognitive approach in language assumes that language is studied not only as a unique object, but also as a means of accessing all the textual processes that take place in the human mind[1,506]. Issues of cognitive linguistics are actively discussed by both foreign and Uzbek linguists. The emergence of cognitive linguistics as a science is DJ. Lakoff, R. Langaker, M. Johnson, E. Related to research by Rosh et al.Ye.S. In Kubryakova's work, on the one hand, the Basic Rules of cognitive linguistics presented in the work of foreign scientists are systematized, while on the other hand, a private concept of language learning has been proposed, the direction, subject and problems of Cognitive Research in Russian linguistics have been established[2,506].